PENERAPAN LAYANAN BIMBINGAN KELOMPOK UNTUK MENGURANGI CAREER INDECISION (KERAGUAN PENENTUAN STUDI LANJUT) PADA SISWA KELAS XI SMA NEGERI 7 BANJARMASIN - Norhidayanti; Rahmawati, Lisa; Mu'jizah, Saudati; Sarpani, Muhammad; Sulistiyana; Muchlisin, Tommy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Career indecision is a condition in which students experience difficulties and uncertainty when determining their future educational pathways. This condition may arise due to inadequate self-understanding, limited information about further education, difficulties in decision-making, and low confidence in educational choices. This study aimed to reduce career indecision among students of class XI through group guidance services. The study employed the Guidance and Counseling Action Research (PTBK) method conducted in three cycles consisting of planning, action, observation, and reflection stages. The participants were eight students identified as experiencing uncertainty in determining further study choices. The findings indicated that group guidance services helped students improve self-understanding, gain broader information about further education, enhance decision-making skills, and strengthen confidence in their educational choices. These improvements were reflected in the observation and process evaluation results, which increased from the fair category in Cycle I to the very good category in Cycle III. Therefore, group guidance services are effective in reducing career indecision among students of class XI.